The effect of leadership style on performance with psychological capital as moderating - Muhammad Aldiansyah; M Giatman; Hasan Maksum; Ambiyar Ambiyar (Indonesian Counselor Association (IKI), 2024)
An organization must have more value in terms of human resources in order to compete with other organizations. The organization in implementing the work program that has been prepared basically always aims to achieve organizational goals. One way is to improve employee performance. Performance is the result or level of success of a person as a whole during a certain period in carrying out tasks. This study was conducted to determine the effect of leadership style on performance with psychological capital as moderating on employees of the Faculty of Sport Sciences, Padang State University. Independent variables in this study include leadership style, while employee performance is used as the dependent variable and psychological capital as a moderating variable. The sampling technique was carried out by saturated sampling which made the entire population as a sample obtained as many as 66 employees at the Faculty of Sports Science, Padang State University. By using an instrument in the form of a questionnaire which is analyzed using SEM-PLS analysis, where the results obtained are leadership style has a significant and positive effect on employee performance. Psychological capital can moderate leadership style on employee performance. It is recommended that the leadership of the Faculty of Sports Science, Padang State University needs to provide development training, update the knowledge of employees, because in filling out the questionnaire the respondents are still low in skillful value compared to the standard procedures that exist in work.